Artificial Intelligence and Its Role in Developing The Educational Process: An Analytical Study of The Advantages and Challenges in Light of Digital Transformations - Faraj, Shara Raouf Saleh Faraj (Sulaimani Journal for Humanities, 2025)
The current study aimed to investigate artificial intelligence and its role in developing the educational process: an analytical study of the advantages and challenges in light of digital transformations. The researcher adopted an analytical approach, utilizing a literature review method by reviewing and analyzing the content of several research papers and peer-reviewed global studies, in addition to monitoring several real-life experiences where artificial intelligence technologies were integrated into the educational environment and scientific theses that examined the topic of artificial intelligence in the educational process during the period between 2022-2025. The research aimed to identify the impact of artificial intelligence applications on planning, teaching methods, and evaluation. It also aimed to identify the features of artificial intelligence and its role in enhancing the educational process amid digital transformations, as well as the negative aspects in light of the fundamental changes and digital revolution that the educational system is experiencing. The results showed that multiple artificial intelligence applications could significantly increase efficiency, with specific applications dedicated to teaching, as they are among the most advanced and widespread AI technologies, capable of generating new data. The texts and audio clips have led to an increase in competency and achievement levels, as this approach centers learning around the student and contributes to enhancing satisfaction and self-confidence, which in turn improves the quality of the educational process. In the field of assessment, applications were dedicated to evaluating students. The results showed that students evaluated through artificial intelligence demonstrated a significant increase in self-efficacy and away in stress. AI applications have a positive impact on enhancing student engagement with the curriculum by personalizing content to suit learners' styles and needs. However, one must be cautious of data and algorithmic biases.
Keywords: artificial intelligence; applications; analytical approach; self efficacy; educational process